ATP-binding cassette transporter 1 C69T and V825I polymorphisms in the development of atherosclerosis: A meta-analysis of 18, 320 subjects. Issue 1 (January 2015) - Yin, Yan-Wei; Wang, Qi; Sun, Qian-Qian; Hu, Ai-Min; Liu, Hong-Li
Abstract Introduction ATP-binding cassette transporter 1 (ABCA1), a member of the ATP-binding cassette family, plays a critical role in the development of atherosclerosis (AS). This meta-analysis was performed to assess the associations of ABCA1 C69T and V825I polymorphisms with AS susceptibility. Materials and methods A comprehensive search was conducted to identify all eligible studies from PubMed, Embase, Web of Science, Cochrane database, CBMdisc, CNKI and Google Scholar. Additionally, hand searching of the references of identified articles was performed. All statistical analyses were done with Review Manager 5.1.4 and Stata 11.0. Results Eleven articles involving 14 studies were included in the final meta-analysis. For the ABCA1 C69T polymorphism, six studies involving 1854 AS cases and 5744 controls were combined showing significant association between this variant and AS risk (for T allele vs. C allele: OR = 1.44, 95% CI = 1.04-1.24, p = 0.005; for T/T vs. C/C: OR = 1.39, 95% CI = 1.12-1.73, p = 0.003; for T/T vs. C/T + C/C: OR = 1.34, 95% CI = 1.09-1.65, p = 0.006; for T/T + C/T vs. C/C: OR = 1.13, 95% CI = 1.01-1.27, p = 0.040). For the ABCA1 V825I polymorphism, eight studies involving 2026 AS cases and 8696 controls were combined. There was no significant association between the variant and AS risk (for I allele vs. V allele: OR = 1.18, 95% CI = 0.90-1.53, p = 0.230; for I/I vs. V/V: OR = 1.29, 95% CI = 0.75-2.23, p = 0.360; for I/I vs. V/I + V/V: OR = 1.40, 95% CI = 0.87-2.26, p = 0.160; for I/I + V/I vs. V/V: OR = 1.15, 95% CI = 1.00-1.33, p = 0.060). Conclusions This meta-analysis suggested that the ABCA1 C69T polymorphism was associated with an increased AS risk. Furthermore, there was no significant association between the ABCA1 V825I polymorphism and AS risk.